The Role of Financial Inclusion in Promoting Small and Medium Enterprise Development: A Case Study of Mwaro Province, Burundi - Jean-Baptiste Innocent Nyangoma; Aline Mukantabana; Dieudonné Habonimana (Journal GoodWill, 2024)
This study investigates the role of financial inclusion in promoting the development of Small and Medium Enterprises (SMEs) in Mwaro Province, Burundi. SMEs are recognized as vital contributors to employment creation, innovation, and economic growth, yet their growth potential is often constrained by limited access to formal financial services. Using a mixed-methods approach combining survey data from 150 SME owners and interviews with financial institutions, this research examines how access to credit, savings facilities, and digital financial platforms influences business performance and sustainability. The findings reveal that financial inclusion significantly enhances SME growth through improved access to working capital, effective cash flow management, and increased investment capacity. Additionally, financial literacy and the use of mobile banking technologies serve as mediating factors that strengthen the relationship between financial access and enterprise development. However, persistent challenges such as high lending rates, insufficient collateral, and low awareness of financial products continue to limit inclusion in rural areas. The study concludes that expanding digital financial infrastructure and implementing financial education programs are crucial strategies for fostering inclusive economic growth. Policy recommendations emphasize collaboration between the government, financial institutions, and development partners to create an enabling environment for SME financing in Burundi.